Antiphospholipid syndrome in patients over 65 years: A comparative study of clinical and biological features and thrombotic relapses. (December 2022) - Masson, Colombe; An Nguyen, Thi T.; Dufrost, Virginie; Audrain, Marie; Hémont, Caroline; Agard, Christian; Artifoni, Mathieu; Connault, Jérôme; Fouassier, Marc; Hamidou, Mohamed; Guedon, Alexis F; Wahl, Denis; et al.
Objective: The aim of the study was to describe clinical and biological characteristics and thrombotic relapses of patients diagnosed with antiphospholipid syndrome (APS) after the age of 65 years, in comparison with patients diagnosed with APS before 65. Methods: This retrospective multicenter study was performed to 2005 from 2017 and included patients diagnosed with APS after the age of 65 years, in accordance with Sydney criteria. We compared these patients with APS patients diagnosed before the age of 65 years, and with control thrombotic patients older than 65 years. Results: Fifty-eight APS patients over the age of 65 years were compared to 127 APS patients aged less than 65 and to 58 controls. In elderly APS versus younger APS, there was a male predominance (58.6% vs 36.2% p = .001); myocardial infarction and lower limb deep vein thrombosis (LLDVT) were more frequent in elderly, respectively, 12.1% versus 1.6% ( p = .005), and 44.8% versus 29.9% ( p = .048). Anticardiolipin antibody (aCL) IgM was more frequently found in old patients compared to younger patients (33.9% vs 18.1%, p = .02), contrary to lupus anticoagulant (LAC) (52.8% vs 66.9%, p = .02). Older patients were more often diagnosed with single positive APS (82.8% vs 59.8% p = .002). The thrombotic relapse free survival was lower in elderly APS patients ( p = .044) compared to younger APS. Elderly APS patients had more recurrent arterial and venous thrombosis ( p = .03) and had poorer overall survival ( p = .004) than elderly controls. Conclusion: In this study, APS was different in patients aged more than 65 years, with a male predominance and more myocardial infarctions and LLDVT at diagnosis. Single antiphopholipid positivity and aCL IgM were more frequent in older patients. Older patient with APS had more thrombotic recurrence during follow-up. Compared to elderly controls, elderly APS patients had more thrombosis recurrences and poorer survival.